Pengaruh Model Pembelajaran Kooperatif Tipe Round Robin Brainstorming Terhadap Hasil Belajar Geografi Siswa Kelas X E 4 di MAN Lima Puluh Kota - Ruslani, Silfia; Rahmi, Lailatur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the influence of the round robin brainstorming type cooperative learning model on the geography learning outcomes of students in class X E 4 MAN Fifty Cities. This study uses a quantitative approach with a quasi-experimental design method of the Nonequivalent Control Group Design type. Sample selection was carried out through a purposive sampling technique with certain criteria, so that the experimental class X E 4 (19 students) and the control class X E 1 (19 students) were obtained. Data is collected through tests, questionnaires, and documentation. The instruments used include tests of 20 objective questions and questionnaires with 20 statements. The data analysis technique used is simple linear regression. The results showed that the average posttest score in the experimental class was 80, with an increase in learning outcomes of 0.54 which was in the medium category. Meanwhile, the control class had an average posttest score of 67.63, with an increase in learning outcomes of 0.12 which was in the low category. The magnitude of the influence of variable X (round robin brainstorming type cooperative learning model) on variable Y (learning outcomes) reached 60.9%, with a significance level of 0.000 < 0.05. This indicates that there is a significant and positive influence of the application of the round robin brainstorming type cooperative learning model on student learning outcomes.